Microfiction Series of Receipt Parinaaz di Kafe Kroasia: A Five-Fragment Narrative Transformation in Digital Humanities - Aryana, Achmad Khobir; Raja, Muhammad; Ghany, Muhammad Tri Bintang Fithrah; Saputra, Surya Widi (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This article examines the transformation of the short story Receipt Parinaaz di Kafe Kroasia by Novia Adibatus Shofah into a microfiction series as a five-fragment narrative transformation within the framework of Digital Humanities. The study aims to transform the short story into five microfiction texts of 50–100 words each, representing the experiential phases of the protagonist, including childhood trauma, the recurrence of memory, the journey to Croatia, solitude in the café, and self-reflection. In this study, a microfiction series is understood as the result of narrative fragmentation and compression, producing interconnected micro-narratives within a unified story world. The research employs a qualitative approach with narrative analysis focusing on the concept of hypertextuality by Gérard Genette and narrative theory of Marie-Laure Ryan. The analytical stages include examining intrinsic narrative elements, segmenting the story into five fragments, and reconstructing the text into five microfiction units. The findings illustrate that the transformation into a microfiction series preserves narrative continuity while restructuring the story into a shorter and more fragmented form. Each microfiction functions as an autonomous script that conveys implicit meanings, while collectively maintaining semantic coherence across the series. The outputs of this study consist of five microfiction scripts and a digital visualization in the form of a flyer, representing a form of digital literary production within Digital Humanities.